VARIASI BAHASA TOKOH DALAM FILM “HARTA TAHTA BORU NI RAJA”: KAJIAN SOSIOLINGUISTIK - Butar-Butar, Putri Herawati; Marlina Agkris Tambunan; Junifer Siregar; Jumaria Sirait; Immanuel Doclas Belmondo Silitonga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to describe language variations in the film Harta Tahta Boru Ni Raja through a sociolinguistic study. Using a descriptive qualitative method, this study analyzed 102 speech data classified based on the aspects of speakers, usage, formality, and means. The results of the study show: (1) The speaker aspect is dominated by personal idiolect, Toba Batak dialect (horas, lae), chronolect in the form of modern slang (baper, ready), and sociolect of student groups (dosping, ospek). (2) The usage aspect includes the journalistic variety of radio broadcasts, academic scientific variety, and military terms. (3) The formality aspect reflects social relations through official, business (consultative), casual, and familiar varieties (bacot, gue-lu). (4) The means aspect includes spoken, telephone, and digital messaging (WhatsApp) varieties. These findings prove that the film authentically portrays the dynamics of language as a social practice that represents Batak ethnic identity amidst the influence of popular culture and the development of communication technology. The diversity of language variations found is significantly influenced by social background, situation, and the purpose of communication between characters.